Interactive Teaching Material Development Training Using Macromedia Flash 8 for Teacher-Working Group Based on ICT in The Elementary School in District of Pontianak City - Hery Kresnadi; Rosnita Rosnita; Asmayani Salimi; Maha Latasa B (JPKM (Jurnal Pengabdian Kepada Masyarakat) UNTAN, 2018)
Devotion to The Society aims to provide understanding and improvement of skills in creating interactive materials using Macromedia Flash 8. The method of activities implemented is in the form of direct practice of creating interactive materials using Macromedia Flash 8 with competent instructors with training materials and to provide direct experience to participants consisting of 21 teachers of members of the Pontianak City ICT Teachers Working Group. After completing the training of interactive learning materials using Macromedia Flash 8, 21 participants already understand and skillful in making flowchart, Scene, and Frame. Meanwhile, to understand and skilled in making Action Script only 11 people only, it is anticipated by the resource by providing action script file directly to participants who have not understood. At the end of the training session, the instructor checks the results of making interactive teaching materials from each participant. Of the 21 participants who successfully completed the teaching materials are only 17 people, from 17 people are only 10 people whose teaching materials can be used, while the 7 people there is a mistake in writing Action Script it. The training of interactive instructional materials using Macromedia Flas 8 is necessary for teachers in elementary schools as it is very useful to improve the competencies needed to address the challenges of the education world in today's information age. The use of Macromedia Flash 8 in evaluating the success of a learning process will increase the excitement of learning for students because more interesting and challenging can also improve the students' thinking process skills.